Determinants of Capital Structure: A Study of the Pharmaceutical Industry in India - Amsaveni, R.; Gomathi, S. (Indian Journal of Finance, 2012)
The capital structure of a company is the combination of debt, equity and other sources of finance that it uses to fund its long-term asset. The key division in capital structure is between debt and equity. The proportion of debt funding is measured by gearing or leverages. There are different factors that affect a firm's capital structure, and a firm should attempt to determine what is optimal, or best mix of financing. But determining the exact optimal capital structure is not a science, so after analyzing a number of factors, a firm establishes a target capital structure which it believes is optimal. The present study aims to analyze the determinants of capital structure in the Indian pharmaceutical industry, with a sample size of 42 companies, which are listed in the BSE for a period from 2000- 2010. The objectives of the studies are to examine the factors influencing the debt and equity mix of the pharmaceutical industry, and to analyze the impact of leverage in capital structure decisions, and to examine the applicability of trade-off and pecking order theories for the Indian pharmaceutical Industry. The Correlation, Regression analysis, and factor analysis have been carried out, taking leverage as the dependent variable. Profitability, growth, size, Business risk, tangibility, NDTS, liquidity, and uniqueness are explanatory variables. The findings of the study suggest that profitability, uniqueness, business risk and liquidity are negatively related to the leverage, while tangibility, growth, size, non-debt tax shields exhibit positive relationship with leverage. Hence, the result of the study is partially supportive of the pecking order and trade-off theory.